Gender differences in intra-household educational expenditures in Malaysia. (January 2016) - Kenayathulla, Husaina Banu
Highlights: Lack of gender differentials in intra-household educational expenditures nationally. In some regions, parents invest more for female children than for male children. Such differences typically occur once children are enrolled in school. It does not seem to be the case that these data describe a "pro-female" bias. Pro-female gap exists in Bumiputera households' schooling decisions. Abstract: Prior studies examining the apparent reduction of the gender gap in education in Malaysia have been based on the gross enrolment rates. This study examines whether there are significant gender differentials in intra-household educational expenditures in Malaysia and whether gender differences vary by ethnicity or geographical region by using the Engel curve framework and the Hurdle model. There is little evidence of gender bias in Malaysia. The findings suggest that while there are no significant gender differences in intra-household educational expenditures nationally, these do exist in some regions, for the 5 to 9 and 10 to 14 age groups. Such differences typically occur once children are enrolled in school. There is evidence of a significant pro-female gap for Bumiputera children ages 15 to 19.